Factors associated with treatment outcomes in anti-snake venom (ASV) administered snakebite patients (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Snakebite is a neglected tropical disease causing many deaths and serious consequences in Asia and Africa. Anti-snake Venom (ASV) is effective to prevent or reverse the venomous effects of snakebites. The aim of this study was to identify the prevalence of venomous snakebites and factors associated with treatment outcomes in a district hospital of Western Terai in Nepal.Method: A single health facility-based retrospective cross-sectional study was conducted with collection of information from the record section of Bhim Hospital, Rupandehi, Nepal. All snakebite cases treated during July 2013 to July 2018 were included. The data on prevalence of snakebite and treatment outcomes were analyzed. Fischer’s exact test and exact logistic regression were performed to identify factors associated with treatment outcomes of venomous snakebites.Result: The prevalence of venomous snakebites was 3.71% (163/4399). Among cases with complete information (N=120), two-third were cured, and one-fourth were referred. Median number of ASV vials used was 12. Age and ASV vials used showed significant positive moderate correlation (r=0.38, p-value